2020
DOI: 10.1177/1073274820904959
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of ALDH1, Bmi1, and OCT4 Expression in Oral Epithelial Dysplasia and Oral Squamous Cell Carcinoma

Abstract: Background: Increasing evidence suggests the involvement of cancer stem cells (CSCs) in both oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Among the various CSC markers, aldehyde dehydrogenase (ALDH) 1, B cell-specific Moloney murine leukaemia virus integration site 1 (Bmi1), and octamer-binding protein 4 (OCT4) have been noted to increase in OSCC. The aim of the study was to analyze ALDH1, Bmi1, and OCT4 expression in OED and OSCC with clinicopathologic correlation and survival anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 68 publications
(107 reference statements)
1
20
0
Order By: Relevance
“…A possible reason for the same seems to be that the prognosis of HNSCC is not entirely changed by the mRNA expression of only a single gene, because the cancer is caused by the accumulation of multiple mutations in various pathways. However, these four genes have shown clinically significant association with the expression of corresponding CSC biomarker proteins in HNSCC over the past 10 years [5,8,[22][23][24][25][26][27][28]. Thus, we analyzed and confirmed the actual association between mRNA expression of these genes and prognosis in TCGA HNSCC cohort, by referring to these ROC curves.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…A possible reason for the same seems to be that the prognosis of HNSCC is not entirely changed by the mRNA expression of only a single gene, because the cancer is caused by the accumulation of multiple mutations in various pathways. However, these four genes have shown clinically significant association with the expression of corresponding CSC biomarker proteins in HNSCC over the past 10 years [5,8,[22][23][24][25][26][27][28]. Thus, we analyzed and confirmed the actual association between mRNA expression of these genes and prognosis in TCGA HNSCC cohort, by referring to these ROC curves.…”
Section: Discussionmentioning
confidence: 83%
“…ALDH1 appears to have protective properties against HNSCC [ 22 ]. In another study, the positive expression of ALDH1 showed significant correlation with lymph node metastasis and poor prognosis [ 25 ]. The positivity of ALDH1 was also found to be correlated with the number of cells undergoing epithelial-mesenchymal transition and metastasis in early stage oral squamous cell carcinoma (OSCC) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that in HNCs, ALDH1 is mainly regulated by retinoic acid compounds and other oncogenic pathways such as MUC1-C/ERK and WNT/β-catenin ( 191 ), but also by the AKT signaling pathway ( 192 , 193 ). ALDH1A1 increases TUBB3 expression, which down-regulates PTEN and promotes cell proliferation, migration, and invasion ( 194 ).…”
Section: Aldh1 and Various Solid Tumorsmentioning
confidence: 99%